Cerebral haemorrhage in preterm neonates: does cerebral regional oxygen saturation during the immediate transition matter?. Issue 5 (11th June 2015) - Baik, Nariae; Urlesberger, Berndt; Schwaberger, Bernhard; Schmölzer, Georg M; Avian, Alexander; Pichler, Gerhard
Abstract : Objectives: To investigate the occurrence of peri/intraventricular haemorrhage (P/IVH) in preterm infants and its potential association with cerebral regional oxygen saturation (crSO2 ) during the immediate transition. Methods: In this two-centre prospective observational cohort study, crSO2 was measured with near-infrared spectroscopy in preterm infants (<32 weeks of gestational age) during the immediate neonatal transition (15 min). In addition, arterial oxygen saturation (SpO2 ) and heart rate (HR) were monitored with pulse oximetry. Cranial ultrasound scans were performed on day 4, day 7 and day 14 after birth and before discharge. Neonates with IVH of any grade (IVH group) were matched to the neonates without IVH (Non-IVH group) on gestational age (±1 week) and birth weight (±100 g). The duration and magnitude of deviation from the 10th centile in crSO2 during immediate transition was analysed and expressed in %minutes. Results: IVH was found in 12 of the included neonates, who were matched to 12 neonates without IVH. There was no difference in SpO2 and HR between these two groups. The duration and magnitude of centiles-deviation of crSO2 was significantly pronounced in the IVH group compared with the Non-IVH group (1870%min vs 456%min). Conclusions: The neonates of the IVH group showed significantly lower crSO2 values during the immediate transition, although there was no difference concerning SpO2 and HR. The additional monitoring of crSO2 during the immediate transition could reveal neonates with higher risk of developing an IVH later in the course.